Analysis of Employee Performance Perceptions at the Agriculture and Fisheries Service of Rejang Lebong Regency - Haryanti, Wenny; Kamaludin, Kamaludin; Nugroho, Sigit (UNIB Press, 2024)
The objective of this study was to evaluate the performance of employees within the Agriculture and Fisheries Service of Rejang Lebong Regency. The assessment focused on Employee Work Objectives (SKP) as a measure of work behavior. Employing a mixed-methods approach, combining descriptive qualitative methods with naturalistic inquiry, data was collected from 100 respondents through questionnaires, interviews, and documentation studies. The analysis, utilizing both descriptive and qualitative methods, revealed commendable overall performance among employees. Specifically, in the areas of service orientation, integrity, commitment, discipline, cooperation, and leadership, employees of the Rejang Lebong Regency Agriculture and Fisheries Service demonstrated high-level performance. These findings underscore the dedication and effectiveness of the workforce in meeting the established objectives.